A New Technique to Diagnose the Geomagnetic Field Based on a Single Circular Current Loop Model. Issue 11 (16th November 2021) - Rong, Z. J.; Wei, Y.; Klinger, Lucy; Yamauchi, M.; Xu, W. Y.; Kong, D. L.; Cui, J.; Shen, C.; Yang, Y. Y.; Zhu, R. X.; Zhong, J.; Chai, L. H.
Abstract: The geomagnetic field originates from interior dynamo currents and can be approximated well by a simple dipolar field in the vicinity of Earth's surface. Given that the dipolar field is induced by a current loop, it is possible to invert the loop parameters by tracing the sampled magnetic field geometry. Drawing on the analysis of field geometric structure with sampled field dataset, we develop, in this study, a new technique to invert the interior current source, which is based on a single circular current loop model. Unlike previous studies, this technique has the ability to separate and solve the optimal loop parameters successively, including the location of the loop center, the loop axis, the radius, and the carried electric current. Applications to the International Geomagnetic Reference Field and the sampled magnetic field dataset by the spacecraft of the Swarm mission demonstrate that our technique‐derived loop center, loop axis, and magnetic moment are consistent with previous estimations by the eccentric dipole model, which shows the reasonability and effectiveness of this technique. Moreover, our technique can be reduced to fit an eccentric dipole model and is particularly useful for inversions of the geometry of interior current sources. Thus, it could be applied widely in the fields of planetary magnetism and palaeomagnetism. Further applications and constraints are discussed, with some cautions given. Plain Language Summary: Most planets in our solar system possess a global dipolar magnetic field. The dipolar field can be approximatively generated by a current loop. The loop's parameters, including the location of the loop center, the loop axis, the radius, and the carried electric current, are key to characterizing the geometry and strength of the dipolar field. However, traditional methods that use least‐square fitting of all loop parameters simultaneously result in multiple local solutions, meaning there is no general way to solve it. By analyzing the sampled magnetic field dataset, we present a novel technique that separates and solves the loop parameters successively. Several tests show that our technique is reasonable and able to be applied in the fields of geomagnetism, planetary magnetism, and palaeomagnetism. Key Points: New technique is developed to diagnose the geomagnetic dipolar field based on a current loop model Technique is able to separate and solve the loop parameters according to the sampled data set of the magnetic field Tests and applications show that technology is effective and applicable and could be applied widely in the fields of planetary magnetism